Clayey soil amendment by hydrophilic nano bentonite for landfill cover barrier: a case study - Qasaimeh, Ahmad; Sharo, Abdulla A.; Bani-Melhem, Khalid (Journal of Environmental Engineering and Landscape Management, 2020)
Methane and carbon dioxide are of major concern as greenhouse gases; the landfills have the problem of controlling these gases. Al Akaider in Jordan is the second biggest landfill suffers controlling gases as it lacks a cover design system. In this work, the main goal is to investigate the appropriateness of amended expansive clayey soil in Irbid as a cover barrier. The expansive soil is unwanted in construction projects, thus the modification of this expelled soil enables using it as a low cost landfill cover barrier. In this research, the effect of adding nano-clay material (Hydrophilic Nano Bentonite) on the geotechnical characteristics, hydraulic conductivity, and gas transport coefficients of the clayey soil are studied. The soil samples were obtained from Irbid city. Unconfined compressive strength and free swelling tests were performed on soil samples with different percentages of nano-clay added in the range (0.1% to 1.2%) by weight. The results indicated that the addition of nano-clay at low percentages increases the strength of expansive soil up to 315 kPa at 0.6% of nano-clay and the swelling potential decreased dramatically with the addition of nano-clay. The optimal percent of nano-clay was found to be 0.6%. The intrinsic permeability of the amended soil was 6.03×10–15 m2. The average values of fluid transport coefficients were determined at 25 °C. The hydraulic conductivity for water was about 6.5×10–10 m/s. Gas conductivity coefficients for CO2 and CH4 were 5×10–9 m/s and 2.5×10–9 m/s respectively. Gas diffusion coefficients for CO2 and CH4 were 3×10–6 m2/s and 4×10–6 m2/s respectively. The results obtained in this research showed compatibility with standards conducted on geosynthetic clay liner (GCL), consequently the amended Irbid soil investigated, can be used as a cover barrier in Al Akaider landfill. These findings can also be generalized to landfills with similar conditions.